(Re)visiting John Dewey and (Re)imagining a Curriculum with the Empty Space of a Haiku - Nguyen, HongNguyen (Gwen) Thi; Slavik, Steve (Journal of the Canadian Association for Curriculum Studies, 2017)
Like the haiku, in which the empty space invites a reader into open and honest communication with the poet, the authors believe that the empty space of curriculum can promote genuine conversations between the learner and the teacher. Relying on Dewey’s concepts of interest, continuity, and interaction in education, the authors develop three aspects of a curriculum that may engender sustained conversations: (a) aspirations of both the teacher and the learner; (b) continuous interaction; and (c) trust and respect between the teacher and learner. Mentoring in teacher education programs is proposed to develop such conversations, in which both mentor and teachers-to-be feel secure and open enough to claim their aspirations.